Embryo-toxic effects of environmental concentrations of chlorpyrifos on the crustacean Daphnia magna - Palma, Patrícia (2013)
Chlorpyrifos is a non-systemic organophosphorus insecticide leading to the inhibition of the enzyme cholinesterase. Nowadays, this insecticide is widely used on a variety of crops and is frequently detected in surface waters around the world. The main aims of this study were to evaluate the effects of this insecticide on the embryonic development of Daphnia magna, and to assess the sensitivity of this endpoint in comparison with the endpoint of the chronic 21-day test. The featured endpoints were the number of offspring per female and abnormalities of both offspring and embryos. Chlorpyrifos exhibited significant toxic effects on the embryonic development manifested in the appearance of abnormalities, including arrested eggs, in 20% of the embryos exposed to a concentration of 0.01 μg L−1. Furthermore, chronic exposition to the insecticide yielded a proportion of offspring abnormalities in later stages of development of about 43% at 0.01 μg L−1. In contrast, a significant reduction in the number of offspring produced per female was only observed above a concentration of 0.03 μg L−1. Hence, these results suggest that developmental abnormality was a more sensitive endpoint than the number of offspring production per female.